Penerapan Model Pembelajaran Group Investigation (GI) berbantuan Media Kahoot untuk Meningkatkan Aktivitas dan Hasil Belajar Akuntansi - Meylin Amanda Simalango; Rini Herliani; Andri Zainal; Ramdhansyah; Haryani Pratiwi Sitompul (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This study was motivated by the low level of students’ learning activities and accounting learning outcomes, which were influenced by the dominance of teacher-centered learning, resulting in limited student engagement during the learning process. This study aimed to improve students’ learning activities and accounting learning outcomes through the implementation of the Group Investigation (GI) learning model assisted by Kahoot. The research was conducted at SMKS PAB 2 Helvetia in the second semester of the 2025/2026 academic year, involving 17 students of class XI AKL. This study employed Classroom Action Research carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation of learning activities and learning outcome tests. The results showed that the percentage of active students increased from 41.17% in the first cycle to 82.35% in the second cycle. In addition, students’ learning outcomes also improved, as indicated by the increase in learning mastery from 29.41% in the pre-test to 76.47% in the first post-test, and reaching 100% in the second post-test. Therefore, the implementation of the Group Investigation learning model assisted by Kahoot was proven to be effective in improving students’ learning activities and accounting learning outcomes.